Impact of Pediatric Acute Otitis Media on Child and Parental Quality of Life and Associated Productivity Loss in Malaysia: A Prospective Observational Study - Crawford, Bruce; Hashim, Siti Sabzah Mohd; Prepageran, Narayanan; Goh, Bee See; Meier, Genevieve; Wada, Keiko; Coon, Cheryl; Delgleize, Emmanuelle; DeRosa, Michael (Adis Open Access, 2017)
Background: Acute otitis media (AOM) affects both child and parental quality of life (QoL). Data on QoL associated with AOM in Malaysia is sparse, and the burden of indirect costs have not been previously reported. Objective: To determine the effect of pediatric AOM on child and parental QoL in Malaysia and its economic impact (indirect costs). Methods: We utilized a set of QoL questionnaires (PAR-AOM-QOL, OM-6, and EQ-5D) combined with questions addressing work/productivity loss and financial costs associated with caring for a child during his or her illness in an observational, multicenter, prospective study. Results: One hundred and ten AOM patients aged ≤5 years were included in the analysis. The majority of respondents were the patient’s mother. Parental QoL was negatively affected for both emotional and daily disturbance scales, but the level of disturbance was low. Using OM-6, the greatest negative impact was on the child’s QoL, followed by caregiver concerns, physical suffering, and emotional distress. Using EQ-5D, a moderately positive relationship between parents’ emotional disturbance and daily disturbance, and a weak, negative correlation between parental emotional disturbance and parental health status was found. Parents with paid employment took an average of 21 h from work to care for their child, at an average cost of 321.8 Malaysian ringgit (US$97) in addition to their contribution to direct medical costs. Productivity losses whilst at work, uncompensated wage losses, and leisure time losses are also reported. Conclusions: This study found that AOM is associated with some negative impact on parental QoL and significant economic impact at both patient and societal levels. The findings provide useful data on healthcare resource utilization and disease burden of AOM in Malaysia.